Pengaruh Penambahan Tepung Gaplek dan Isolat Bakteri Asam Laktat dari Cairan Rumen Sapi PO Terhadap Kualitas Silase Rumput Gajah (Pennisetum purpureum) - Ismail Jasin (Jurnal Agripet, 2015)
(The effect of cassava meal and Lactic Acid Bacteria isolated from rumen liquid of PO cattle on napier grass silage quality)ABSTRACT. The objective of this study was to evaluate the effect of cassava meal as carbohydrate source and inoculums of lactic acid bacteria incubated from PO cattles rumen liquid on the quality of Napier grass (pennisetum purpureum) silages. The research was conducted at Ujung-ujung village Pabelan District Semarang Regency. Feed analysis was carried out in of Biochemical Nutrition, Animal Feed Science, Animal Science Faculty, Gadjah Mada University. This study was assigned into Completely Randomized Design with 4 treatments and 3 replicated. The treatments were addition of cassava meal and inoculums of lactic acid bacteria level into the Napier grass; 0, 1, 3 and 5% (w/w) and incubated for 30 days. Data were analyzed using analysis of variance (ANOVA) and the significant effect was tested by Duncans Multiple Range Test. The results showed that the addition of 1 5% cassava meal significantly affected (P0,05) lactic acid content, pH, and NH3 concentration. Should be revised However, among the treatment groups of 1, 3 and 5 % of cassava meal was not significantly (P0,05) different on the lactic acid content, pH and NH3 concentration.